2013
DOI: 10.1007/s10815-013-9984-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the site of assisted hatching on vitrified-warmed blastocyst transfer cycles: a prospective randomized study

Abstract: Purpose To assess the effect of assisted hatching (AH) site on the clinical outcomes in vitrified-warmed blastocyst transfer cycles. Methods A total of 160 women who underwent vitrifiedwarmed blastocyst transfer cycles were randomized to either the ICM group (AH performing at the site near the inner cell mess, ICM), or the TE group (AH performing at the site opposite to the ICM). AH with laser zona drilling was performed 20 or 30 min after thawing once the ICM can be detected. Clinical pregnancy rate, implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…Some researchers performing AH at a site close to the ICM observed a higher rate of complete hatching in human vitrified blastocysts 8 . Interestingly, further study found the AH site had no influence on implantation, clinical pregnancy, or live birth rate 11 . Others found the site of AH did not influence the rate of completed hatching by blastocysts in mice 9 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some researchers performing AH at a site close to the ICM observed a higher rate of complete hatching in human vitrified blastocysts 8 . Interestingly, further study found the AH site had no influence on implantation, clinical pregnancy, or live birth rate 11 . Others found the site of AH did not influence the rate of completed hatching by blastocysts in mice 9 .…”
Section: Discussionmentioning
confidence: 91%
“…Although these two hatching patterns were both observed in IVF and ICSI embryos, they have no effect on embryo implantation. In human vitrified-warmed blastocysts, the assisted hatching (AH) site (near or opposite to the ICM) did not affect blastocyst implantation or subsequent pregnancy and live birth rates 11 . Conversely, others found that ZP opening close to the ICM was associated with a higher implantation and pregnancy rate in humans 12 .…”
mentioning
confidence: 99%
“…LAH was performed within 20-30 min after blastocyst thaw once the ICM was detected. There was no difference in IR, PR, LBR, or monozyogotic twin rate between the two groups [9].…”
Section: The Effect Of the Site Of Ah On Outcomesmentioning
confidence: 73%
“…Following introduction of the best technique to be laser AH, studies started to investigate the partial or total zona hatching on the ART outcome (23)(24)(25)(26). Additional studies on the frozen-thawed embryo cycles revealed variable results (27,28). Age also has been an issue, and assessed in several further studies to determine whether there is an optimal age group, who would benefit from AH, again these studies showed variable results (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%